The ISOLDE facility. (1st August 2017) - Catherall, R; Andreazza, W; Breitenfeldt, M; Dorsival, A; Focker, G J; Gharsa, T P; T J, Giles; Grenard, J-L; Locci, F; Martins, P; Marzari, S; Schipper, J; et al.
Abstract: The ISOLDE facility has undergone numerous changes over the last 17 years driven by both the physics and technical community with a common goal to improve on beam variety, beam quality and safety. Improvements have been made in civil engineering and operational equipment while continuing developments aim to ensure operations following a potential increase in primary beam intensity and energy. This paper outlines the principal technical changes incurred at ISOLDE by building on a similar publication of the facility upgrades by Kugler (2000 Hyperfine Interact. 129 23–42). It also provides an insight into future perspectives through a brief summary issues addressed in the HIE-ISOLDE design study Catherall et al (2013 Nucl. Instrum. Methods Phys. Res. B317 204–207).